Psychology for Musicians: Understanding and Acquiring the Skills - Lehmann, Andreas C.; Sloboda, John A.; Woody, Robert H. (Oxford Oxford University Press, 2007)
What is it that accounts for the differences between musical beginners, advanced music makers, and world class performers? Virtually everyone likes music and has the capacity to be musical in some way (despite what some may say about themselves). Yet far fewer people come to be so involved with it that they identify themselves as musicians, and fewer still become musicians of international class.Psychology for Musicians provides the basis for answering this question. Examining the processes that underlie the acquisition of musical skills, Lehmann, Sloboda, and Woody provide a concise, accessible, and up-to-date introduction to psychological research for musicians.
Keywords: Music psychology